Psychological health of healthcare workers and national vaccination programme: A conceptual study - Healthcare Workers and National Vaccination Programme - Santhi Raghavan,; Ashwini M. Madawana, (2021)
Stress levels can be raised by psychosocial risks, which can lead to physical and mental health problems. Low motivation, exhaustion, anxiety, sadness, burnout, and suicidal ideation are all possible psychological responses. Malaysia has one of the highest COVID-19 immunisation rates in the world. Although this is a huge accomplishment, we must keep in mind that it adds to the taskforce's workload. Between January 2019 and May 2020, there were an average of two suicide deaths per day. The Royal Malaysia Police Force, on the other hand, reported that suicide rates had doubled in the first five months of 2021. A mass vaccination centre in Kuala Lumpur was closed on August 6, 2021, after over 200 medical staff and volunteers tested positive for the coronavirus. Fear is rising among healthcare workers as a result of a previous occurrence like this, and the current emergence of the Delta strain of the Virus, and now the Omicron, can only alarm the healthcare family. According to a study conducted by American International Assurance (AIA Vitality), majority of Malaysian workforce unable to get enough sleep. One out of every ten Malaysian representatives is nervous or discouraged, with the majority of them being in their twenties and thirties. As is the case during a pandemic, healthcare workers are overworked. They must deal with the effects of public misconception, face stress from relatives, fear of contracting the obscure illness and becoming a carrier of the illness, and now seek protection from the Personal Protective Equipment (PPE) and vaccinations to which they have adhered during vaccination programmes. Frontline workers' mental health issues, particularly burnout and fear, should be addressed by policymakers. Future national and organisational interventions must include providing adequate social support, building self-efficacy and resilience, and ensuring frontline work willingness. (Abstract by authors)